Intralesional injection of mitomycin C following internal urethrotomy of de novo bulbar urethral stricture:New experience using a novel adjustable-tip needle. Issue 4 (2nd October 2021) - Noureldin, Yasser A.; Fathy, Abdallah; Ahmed, Shabib; Shaer, Alaa El; Ali, Saad; Saki, Zakaria; Sebaey, Ahmed
ABSTRACT: Objectives : To assess the efficacy of intralesional injection of mitomycin C (MMC), using a novel adjustable-tip needle, following visual internal urethrotomy (VIU) in reducing the recurrence of de novo bulbar urethral stricture disease (USD). Patients and methods : Using closed envelopes, 50 patients diagnosed with bulbar USD of <2 cm were randomised to undergo either VIU with MMC injections (Group-A) or VIU alone (Group-B). The urethrotomy was performed under direct vision using a cold-knife and incisions were made at the 12-, 4-, and 8-o'clock positions followed by intralesional injection of 10 mL MMC (0.4 mg/mL) using a novel depth-adjusting needle. All patients were objectively evaluated pre- and postoperatively at 3, 6, and 9 months using uroflowmetry (maximum urinary flow rate), post-void residual urine volume, and retrograde urethrography. Results : Of all 50 patients; five missed follow-up (four in Group-A, one in Group-B), hence 45 cases were available for analysis (21 in Group-A and 24 in Group-B). The mean (SD) age of patients was 34.33 (7.2) and 37.7 (10.2) years in Group-A and Group-B, respectively ( P = 0.22). The depth-adjusting needle was easy to use and all injections were successfully completed. In terms of stricture recurrence, there was significant decrease in Group-A (three patients, 14.3%) compared with Group-B; (12 patients, 50%) ( P = 0.01). On multivariate Cox regression analysis, the VIU with MMC was found as a sole factor associated with marked decrease in stricture recurrence (hazard ratio 0.23, 95% confidence interval 0.06–0.93; P = 0.04). The Kaplan–Meier survival curve for recurrence-free survival showed a statistically significant difference between both groups (85.7% vs 50.0%; chi-squared = 7.079, P = 0.008). Conclusion : The use of a novel depth-adjusting needle was easily applied and MMC injection after VIU resulted in a significantly lower recurrence of de novo bulbar USD. Abbreviations : MMC: mitomycin C; PVR: post-voiding residual urine; Qmax : maximum urinary flow rate; RFS: recurrence-free survival; RUG: retrograde urethrography; USD: urethral stricture disease; VIU: visual internal urethrotomy